The Effect of Health Education with Audio Visual Media on the Ability of Toilet Training for Preschool Children - Ferasinta Ferasinta; Leni Rozani; Andry Sartika; Endah Zulya Dinata (KHD Production, 2025)
Toilet training is one way to teach children to control bowel movements and urine. It is important to teach children to be independent in ablution and defecation. Toilet training is suitable for teaching children good habits from an early age. This study aimed to determine whether health education with audiovisual media affects the independence of toilet training in preschool children. The research method used is a pre-experimental design pretest and posttest group with a quantitative approach. The population of this study was all preschool, as many as 27 people. It shows that Before the intervention, it was found that independence had not been developed (BB) 0%, independence began to develop (MB) 25.9%, independence developed as expected (BSH) 40.7%, and independence was very well developed (BSB) 33.3%. It shows that after the intervention showed that independence did not develop (BB) 0%, independence began to develop (MB) 0%, independence developed as expected (BSH) 7.4% independence is very well developed (BSB) 92.6%. It shows that the average score before and after providing health education is -4.519, the standard deviation is 1.528, and the p-value is 0.000. Health education and audiovisual media influence the independence attitude of preschool children. Policymakers and healthcare institutions should prioritize incorporating digital tools into community health programs, particularly in underserved areas, to promote equitable access to essential developmental support.